Early childhood transmission of hepatitis B prior to the first hepatitis B vaccine dose is rare among babies born to HIV-infected and non-HIV infected mothers in Gulu, Uganda. Issue 22 (19th May 2017) - Seremba, E.; Van Geertruyden, J.P.; Ssenyonga, R.; Opio, C.K.; Kaducu, J.M.; Sempa, J.B.; Colebunders, R.; Ocama, P.
Abstract: Background: Hepatitis B (HBV) in sub-Saharan Africa is believed to be horizontally acquired. However, because of the high HBV prevalence in northern Uganda, no hepatitis B vaccination at birth and no access to HBV immunoglobulin, we hypothesize that vertical transmission also could also play an important role. We therefore investigated the incidence of HBV among babies presenting for their first HBV vaccine dose in Gulu, Uganda. Methods: We recruited mothers and their babies (at least 6-week old) presenting for their postnatal care and first HBV vaccine dose respectively. Socio-demographic and risk factors for HBV transmission were recorded. Mothers were tested for Hepatitis B core antibody (anti-HBc-IgG) and hepatitis B surface antigen (HBsAg). HBsAg-positive sera were tested for hepatitis B e antigen (HBeAg) and HBV viral load (HBVDNA). Babies were tested for HBsAg at presentation and at the last immunization visit. A sample of HBsAg-negative babies were tested for HBVDNA. Incident HBV infection was defined by either a positive HBsAg or HBVDNA test. Chi-square or fisher's exact tests were utilized to investigate associations and t -tests or Wilcoxon rank-sum test for continuous differences. Results: We recruited 612 mothers, median age 23 years (IQR 20–28). 53 (8.7%) were HBsAg-positive and 339 (61.5%) were anti-HBc-IgG-positive. Ten (18.9%) of the HBsAg-positive mothers were HBeAg-positive. Median HBVDNA levels of HBV-infected mothers was 5.7log (IQR 4.6–7.0) IU/mL with 9 (17.6%) having levels ≥ 10 5  IU/mL. Eighty (13.3%) mothers were HIV-infected of whom 9 (11.5%) were co-infected with HBV. No baby tested HBsAg or HBVDNA positive. Conclusion: Vertical transmission does not seem to contribute substantially to the high HBV endemicity in northern Uganda. The current practice of administering the first HBV vaccine to babies in Uganda at six weeks of age may be adequate in control of HBV transmission.